SNOWPIERCER FILM AS A REFLECTION OFCLASS STRUGGLE: A MARXIST STUDY IN THE CONTEXT OF POPULAR CULTURE - Suandi, Ercika Fitria; Khairunnisa, Farah; Alfazari, M. Rafl (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2025)
Snowpiercer (2013), directed by Bong Joon-ho, is a science fiction film set in a post-apocalyptic world where the remnants of humanity inhabit a massive train that perpetually circles the globe. The train functions not only as a means of survival but also as a representation of an entrenched and highly stratified social hierarchy. The film portrays systemic inequality and class conflict, making it a compelling subject for analysis through a Marxist theoretical lens. This article examines how class division, labor exploitation, and the struggle between the oppressed and the ruling elite are depicted through the film’s narrative and character development. Using a descriptive-qualitative method and a critical Marxist approach, this study reveals that Snowpiercer serves not merely as visual entertainment but as a potent medium for social critique—challenging capitalist systems and the ideological domination reinforced by structural inequality. The film’s portrayal of resistance among the lower class suggests the emergence of collective consciousness as a response to systemic injustice. As a work of popular literature, Snowpiercer demonstrates how cinema can transmit ideological messages, foster social awareness, and provoke critical reflection on contemporary conditions. Accordingly, the film merits recognition not only as a creative work but also as a politically and educationally relevant tool that stimulates public consciousness.